Peri-urban Land Transactions : Everyday Practices and Relations in Peri-urban Blantyre, Malawi - Jimu, Ignasio Malizani (Book collections on Project MUSE., 2012)
This book explores the changing land relations in the peri-urban villages of Blantyre in Malawi. It questions and debates how and why the peri-urban villages have become the locus of the selling and buying of customary land, the practices and also the relations involved. The book provides rich ethnographic insights on the commodification of land relations, custom, practices, disputes and social relations between land sellers, land buyers, traditional leaders, and intermediaries. The transactions draw strength from the growing peri-urbanization and monetization of social relations, both of which push towards land decisions at family and individual levels. Bigger groups like the village, clan or extended family have minimal, if not symbolic role only. Village headmen benefit materially by taking gifts (signing fee) rationalized by custom on reciprocity, while estate agents claim commission. Numerous constraints are negotiated about the ownership, rights to sale, multiple selling and the use and sharing of land money. Peri-urban land transactions offer scope for examining a wider range of social and economic relations, and the subtle ways in which the state infiltrates the everyday lives of actors. Overtime, the practices reproduce but also transform land relations in significant but less appreciated ways.